Usaha Wali Kelas Dalam Membangun Ikatan Emosional Terhadap Murid Baru Pada Masa COVID 19 di SMP Muhammadiyah 1 Banjarbaru - Surawardi Surawardi; Annisa Yunani (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2022)
Homeroom teacher's efforts in building emotional bonds with new students during the Covid-19 pandemic at SMP Muhamadiyah1Banjarbaru require various tricks and efforts by homeroom teachers in building emotional bonds with new students so as to create a comfortable atmosphere in learning and children can quickly adapt with the new school environment even though with a different atmosphere that has never happened before and is unimaginable in the minds of students, parents, and teachers about online learning during the Covid-19 pandemic at SMP Muhammadiyah 1Banjarbaru. The role and effort of the homeroom teacher as the central party responsible for the smooth learning process in the online classroom requires maximum effort in building emotional bonds with new students so that they feel comfortable learning in new situations and new ways. Besides that, as a homeroom teacher, it is necessary to carefully examine the possible supporting and inhibiting factors in an effort to build emotional bonds so that learning can take place optimally even with uncomfortable situations and conditions that require adjustments that are not easy and also not cheap because they have to prepare equipment. IT, where both schools and the community, in this case, parents and students, do not all have adequate facilities in responding to and dealing with the COVID-19 situation.The homeroom's efforts in an effort to build emotional bonds with new students at SMP Muhammadiyah Banjarbaru can approach new students in order to create emotional bonds between homeroom teachers and students through specialization class programs, FORTASI (Ta'aruf and Information Forums), podcasts, cadets of jasmine BK assistance, approach through social media and class associations, and zoom sharing. The program has to support and inhibiting factors, while the supporting factors are teachers, students, and parents who are already familiar with technology, as well as adequate facilities. Parental concern for children's education. While the inhibiting factor is the existence of these programs, the homeroom teacher must work extra outside of his duties as a homeroom teacher.Keywords: Effort, build bonds as well as emotional.